2019
DOI: 10.1152/ajpendo.00528.2018
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type-selective exercise effects on AS160 phosphorylation

Abstract: Earlier research using muscle tissue demonstrated that postexercise elevation in insulin-stimulated glucose uptake (ISGU) occurs concomitant with greater insulin-stimulated Akt substrate of 160 kDa (AS160) phosphorylation (pAS160) on sites that regulate ISGU. Because skeletal muscle is a heterogeneous tissue, we previously isolated myofibers from rat epitrochlearis to assess fiber type-selective ISGU. Exercise induced greater ISGU in type I, IIA, IIB, and IIBX but not IIX fibers. This study tested if exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…A method was recently described using rat skeletal muscle that enables the measurement of glucose uptake and fiber type based on myosin heavy chain isoform expression in a single muscle fiber [11,12], but it is unlikely these analyses would be feasible using single fibers from mouse skeletal muscle. Rats have also proven to be extremely valuable for detecting a potential role for AS160 in the processes responsible for improved insulin sensitivity in skeletal muscle [13][14][15][16], so information about both male and female AS160-KO rats will be useful for future mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…A method was recently described using rat skeletal muscle that enables the measurement of glucose uptake and fiber type based on myosin heavy chain isoform expression in a single muscle fiber [11,12], but it is unlikely these analyses would be feasible using single fibers from mouse skeletal muscle. Rats have also proven to be extremely valuable for detecting a potential role for AS160 in the processes responsible for improved insulin sensitivity in skeletal muscle [13][14][15][16], so information about both male and female AS160-KO rats will be useful for future mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that the effect of acute exercise on insulin-stimulated glucose uptake is fiber type-specific in skeletal muscle from healthy rats (9). A subsequent study evaluated fiber type-selective AS160 phosphorylation in insulin-stimulated muscles from healthy rats and reported that those fiber types with exercise-induced improvement in insulin-stimulated glucose uptake were also characterized by greater AS160 phosphorylation (61). These findings provided evidence at the fiber type-specific and cellular levels consistent with the idea that AS160 plays a role in the increased insulin sensitivity after exercise in insulin-sensitive muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research indicated that acute exercise can increase AS160 phosphorylation in muscles from insulin-resistant rats and humans (11,44), but the effects of exercise on fiber type-specific AS160 phosphorylation have not been reported. The evidence that exercise effects on AS160 phosphorylation are fiber type-specific in muscles from healthy rats (61) and that exercise effects on insulin-stimulated glucose uptake is fiber type-specific in muscles from insulin-resistant rats (43), provides a clear rationale for evaluating fiber-type-specific signaling processes in insulin-resistant muscle after exercise. Therefore, our first aim was to evaluate fiber-type-specific effects of exercise (both immediately postexercise and 3-h postexercise with and without insulin) on the phosphorylation of key signaling proteins (AMPK, Akt, and AS160) that have been implicated in the regulation of exercise effects on skeletal muscle glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al . (2019) reported increased TBC1D4 Ser704 phosphorylation in type I and type II fibres, but not type IIx (a subset of type II fibres) 3.5 h after exercise under insulin‐stimulated conditions. However, studies examining the underlying molecular signalling that may potentially distinguish type I and type II fibres from each other during recovery from exercise in human subjects are sparse.…”
Section: Skeletal Muscle Insulin‐signalling and Fibre Typesmentioning
confidence: 99%